The Just City Approach and Urban Transformation: The Case of Esenler, Istanbul - Yunus Çolak (İnsan & Toplum)
The problems emerging with the development areas of contemporary cities and urban trans- formation is a significant field of debate. The priorities in urban development and transformation have increased the importance of the points of view debated at the political level about planning regarding how the mobility produced in the space as a result of interventions made with public instruments is to be managed, and regarding what type of planning decisions are possible. The aim of this study is to reveal the just city approach as one of the recent theoretical approaches in planning; to show the normative views developed around this approach; and to evaluate urban transformation on the basis of this approach. The just city approach is evaluated with the case of Havaalanı neighborhood in Istanbul’s Esenler district, which underwent one of the first urban transformation projects. The study is based on in depth interviews held with local managers of urban transformations, contractors, residents of the district and representatives of non-governmental organizations active in the district. Alongside the necessity for considering the urban justice in urban transformation practices that are assumed to be a model for development, the search for principles to meet this need have also been the basic focus of this study. The approaches treating urban planning with concern for justice will put the urban transfor- mation practices on a solid and accurate ground. Policies with such principles that ensure justice have to be developed to sustain this approach.